汉语句末语气词在反语认知中的作用 ——基于自闭症儿童的实验研究: Roles of the Sentence-final Particles in Cognition of Irony ——Based on the Test of Children with Autism Spectrum Disorders - Di, Zhang; Xiangyan, Wu; Shuzhen, Chen; Kuifeng, Gao (ERUDITE: Journal of Chinese Studies and Education, 2020)
自闭症儿童在反语理解上具有一定的缺陷，本文主要从韵律这种话语线索去研究自闭症儿童对反语的理解。但汉语自闭症儿童在利用韵律线索上相对有限，而句末语气词的语用功能则起到一定的作用。本研究使用三个测量指标（态度、话语真实意图和语言现象解释），考察高功能自闭症儿童利用句末语气词“啊”对反语不同类型进行理解的情况。研究发现,高功能自闭症儿童在反语理解上与普通儿童具有显著差异。语言线索句末语气词只能对高功能自闭症儿童能够理解并判断的反语批评起作用，起到一个提示或者引起注意的作用；而对普通儿童来说，句末语气词对反语表扬的作用较为显著。这表明两组儿童采用不同的策略来理解反语，之间的差异可以使用心理理论、话语频率和认知机制进行解释。 Abstract Children with Autism Spectrum Disorders (ASD) have some shortcomings in the understanding of irony. It’s mainly from the prosody, a kind of language cue, to study the understanding of irony. However, Chinese-speaking children with ASD are less capable of using prosodic cues for irony comprehension, and sentence-final particles (SFPs) may be used for this pragmatic function. This study used three measurement indicators (the attitude, intention and language explanation) to examine the effects of the SFPs on the comprehension of different types of irony between the High-functioning Autism Spectrum Disorder (HFASD) and the Typical Development (TD) children group. The study found there was a significant difference on the irony comprehension between two groups. Language cues SFPs can only play a role in the irony which HFASD children can make the understanding and judgment by. And for TD children, the SFP made a significant effect on the irony of compliment. It shows that two groups used different treatment strategies to understand the irony. The differences were discussed by the theory of mind, the frequency of utterance and the rule of cognition. Keywords: Sentence-final particles, Children with Autism Spectrum Disorder, Irony, Cognition, Theory of Mind